Monitoring spatiotemporal trends in intertidal bedforms of the German Wadden Sea in 2009–2015 with TerraSAR-X, including links with sediments and benthic macrofauna - Adolph, Winny; Schückel, Ulrike; Son, Chang Soo; Jung, Richard; Bartholomä, Alexander; Ehlers, Manfred; Kröncke, Ingrid; Lehner, Susanne; Farke, Hubert (Geo-Marine Letters, 2017)
Satellite synthetic aperture radar (SAR) holds a high potential for remote sensing in intertidal areas. Geomorphic structures of the sediment surface generating patterns of water cover contrasting with exposed sediment surfaces can clearly be detected. This study explores intertidal bedforms on the upper flats bordering the island of Norderney in the German Wadden Sea using TerraSAR-X imagery from 2009 to 2015. Such bedforms are common in the Wadden Sea, forming crests alternating with water-covered troughs oriented in a north-easterly direction. In the western Norderney area, the crest-to-crest distance ranges from 50–130 m, and bedform length can reach 500 m. Maximum height differences between crests and troughs are 20 cm. A simple method is developed to extract the water-covered troughs from TerraSAR-X images for spatiotemporal analysis of bedform positions in a GIS. It is earmarked by unsupervised ISODATA classification of textural parameters, contrasting with various algorithm-based methods pursued in earlier studies of waterline detection. The high-frequency TerraSAR-X data reveal novel evidence of a bedform shift in an easterly direction during the study period. Height profiles measured with RTK-DGPS along defined transects support the findings from TerraSAR-X data. First investigations to characterise sediments and macrofauna show that benthic macrofauna community structure differs significantly between crests and troughs, comprising mainly fine sands. Evidently, bedform formation has implications for benthic faunal diversity in back-barrier settings of the Wadden Sea. SAR remote sensing provides pivotal data on bedform dynamics.
CRIS-Team Scopus Importer:2024-03-18